Assessing Deliberative Pedagogy: Using a Learning Outcomes Rubric to Assess Tradeoffs and Tensions - Sara A. Mehltretter Drury (Journal of Deliberative Democracy)
Teaching deliberative decision-making is a method of encouraging students to think critically, engage public problems, and engage in both public speaking and public listening. College instructors have begun to use deliberation as a pedagogical tool, yet further research is needed to understand the learning outcomes of deliberative pedagogy. We argue that the deliberative principle of “understanding tradeoffs and tensions” is a key learning outcome of deliberative pedagogy, and demonstrate an avenue for evaluating it through a learning outcomes rubric, and through critical-interpretative methods of rhetorical criticism. In our analysis, we demonstrate that students with prior training in deliberation achieve higher levels of understanding tradeoffs and tensions through their rhetorical behaviors of embodying a deliberative perspective, expressing inclusivity, and working through public problems.